2009
DOI: 10.1002/jmv.21596
|View full text |Cite
|
Sign up to set email alerts
|

A long‐term survey on the distribution of the human rotavirus G type in Thailand

Abstract: The distribution of the G type of human rotavirus was surveyed in Thailand between July 1993 and June 2007. A significant yearly change in the distribution of the G type distribution was found. From 1993-1994 to 1998-1999, the G1 type was the most dominant. In 1999-2000, G9 began to appear at a high frequency. In 2000-2001, 2001-2002, and 2002-2003, G9 was very common. In 2003-2004, G1 became the most prevalent type again, and since then it has been detected at the highest frequency. G12 strains, which were fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 43 publications
4
26
0
Order By: Relevance
“…our previous study, all the 1,204 G1, 38 G3, 89 G4, and 579 G9 HuRVAs showed a long RNA pattern[Pongsuwanna et al, 2010]. our previous study, all the 1,204 G1, 38 G3, 89 G4, and 579 G9 HuRVAs showed a long RNA pattern[Pongsuwanna et al, 2010].…”
mentioning
confidence: 64%
See 2 more Smart Citations
“…our previous study, all the 1,204 G1, 38 G3, 89 G4, and 579 G9 HuRVAs showed a long RNA pattern[Pongsuwanna et al, 2010]. our previous study, all the 1,204 G1, 38 G3, 89 G4, and 579 G9 HuRVAs showed a long RNA pattern[Pongsuwanna et al, 2010].…”
mentioning
confidence: 64%
“…G8 is combined also with P[1], P[4], P[6], P [8], or P[14]. In Thailand, only one G8 strain was detected in 2,560 HuRVA specimens between 1993 and 2007 [Pongsuwanna et al, 2010]. G8 is rare worldwide, but there have been relatively high rates of detection in Asian and African countries [Esona et al, 2010;Delogu et al, 2013;Kargar et al, 2014].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RVA vaccination in national immunization programs has not been started in Thailand, although a monovalent RVA vaccine (Rotarix) was introduced in a pilot study in 2011 in Sukhothai province, Thailand . The major G/P types in Thailand have been shown to be G1P[8], G2P[4], G3P[8], G8P[8], and G9P[8], and the predominant G/P type changed after 2000: G1P[8] was predominant in 1993 to 1999, G2P[4] in 1999 to 2000, G9P[8] in 2000 to 2004, G1P[8] in 2005 to 2009, G3P[8] in 2009 to 2011, and G1P[8] in 2012 to 2014, respectively . There is a general correlation between G/P type and RNA pattern on polyacrylamide gel electrophoresis (PAGE): the G1P[8], G3P[8], G4P[8], and G9P[8] strains show a long RNA pattern, and the G2P[4] strains exhibit a short RNA pattern .…”
Section: Introductionmentioning
confidence: 99%
“…G12 strains were rare in humans and after being first detected in 1987-1988 from Philippines [89], emerged as an important g-genotype in the last few years. In recent years, studies from India, Bangladesh, Nepal, Argentina and other parts of the world have reported increasing incidence of another potentially emerging strain G12, with a variety of P types such as P [6], P [8] and P [9] [6,8,19,35,58,67,68,70,71,73,80,82,89]. During routine surveillance of diarrhea caused by rotavirus in Calcutta, India, the emergence of a novel type of human rotavirus, serotype G12, was reported [80].…”
Section: Emergence Of Serotype G9 and G12 Rotavirusesmentioning
confidence: 99%